Silent Crusade? Indigenous Women in Taiwanese Indigenous Movements - Jolan Hsieh (Universitat de Barcelona, 2016)
Among the various indigenous rights movements across different times in Taiwan, the presence of indigenous women often goes obscure. Although in recent years there has been a great deal of publications on Taiwanese indigenous movements, some of the literature —constructed under the structure of the indigenous knowledge system—, while insisting on the status and value of indigenous autonomy, tend to overlook the historical context in Taiwanese society of indigenous women who participated in social movements. What are the issues of concern? This paper primarily serves to reveal the “silent crusades” and to bring forward the directions of interests of the indigenous women’s movements by analyzing related reports, autobiographies, interview transcripts, texts, etc. spanning over two decades and published in the weekly newspaper of the Presbyterian Church in Taiwan (PCT), Taiwan Church News, in addition to in-depth interviews with the leaders of indigenous women’s social movements.